2007
DOI: 10.1002/chin.200746011
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Efficiency of Iron(III) Oxides in Decomposition of Hydrogen Peroxide: Competition Between the Surface Area and Crystallinity of Nanoparticles.

Abstract: Controlled decomposition of FeC2O4·2H2O in air at 175°C allows the simple synthesis of amorphous Fe2O3 nanoparticles and their controlled one-step crystallization to α-Fe2O3 (hematite). Depending on the reaction time, nanopowders differing in surface area and particle crystallinity are prepared. The samples are characterized by XRD, HRTEM, SAED, and 57 Fe Moessbauer spectroscopy, and their catalytic activity in the decomposition of H2O2 is studied. The amorphous nanopowder with the largest surface area shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 1 publication
2
52
0
Order By: Relevance
“…These nanoparticles provide greater reaction rates than their bulk counterparts (27), and with the addition of H 2 O 2 , many of these oxides are capable of catalyzing the oxidative degradation of organic compounds (28). Furthermore, by using membranes impregnated with these inexpensive catalysts, additional separations for nanoparticle removal can be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…These nanoparticles provide greater reaction rates than their bulk counterparts (27), and with the addition of H 2 O 2 , many of these oxides are capable of catalyzing the oxidative degradation of organic compounds (28). Furthermore, by using membranes impregnated with these inexpensive catalysts, additional separations for nanoparticle removal can be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Among the transition metal oxides, hematite (α-Fe 2 O 3 ) has attracted great interest due to its favorable properties, such as low cost, good stability, nontoxicity, and environmental friendly properties. It has been studied for applications in Li-ion batteries [7][8][9][10], supercapacitors [11][12][13], magnetic materials [14,15], catalytic agents [16], gas sensors and so on [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…S12) showed that a doublet spectrum appeared after 1 day. According to the hyperfine parameters at room temperature (Table 1), such a doublet was the Mossbauer spectra of Fe 3+ oxides or oxyhydroxides [47][48][49] transfer between adsorbed Fe 2+ and structural Fe oxide occurred in the absence of Fe 0 or other chemicals which can create galvanic cells with structural Fe oxide. It means this spontaneous electron transfer was not driven by potential difference.…”
Section: Interface Electron Transfer and Fe Species Transformationmentioning
confidence: 99%